Social perception from the point of view of the races - Kadim, Algarrawi Marwa (Eximia, 2023)
This study explores (1) Measuring social perception (I am myself). (2) Measuring the social perception (the Arab). (3) Measuring the social perception (Russian). (4) Identifying the correlation between the Arab and Russian self in the social perception scale. For the purpose of statistical analysis of the items of the Philip Carter Personality Test to extract standard characteristics, the test was applied to a sample of (1, 00) male and female students who were selected using the cluster sampling method. Based on the results that were extracted according to the paragraph response theory, the researcher concluded the following: (1) The T-test for a sample and population showed that the research sample for (I am myself) was negative because the calculated T-value was less than the theoretical tabular value. The second goal: measuring social perception of each characteristic of (Arabic): The t-test for a sample and population showed that the research sample for (I am myself) was negative because the calculated t-value was less than the tabulated value. The third goal: measuring the social perception of each characteristic of (Russian): The t-test for a sample and population in Table No. (10) Showed that the research sample for (I am myself) was negative because the calculated t-value was less than the tabulated value. Fourth goal: To identify the correlational relationship between (I myself, Arab, Russian) in the social perception scale. : By observing the results, it became clear that there is a (direct) and statistically significant relationship between (I am myself and the Arab, the Arab and the Russian, and I am myself and the Russian). This means that there is a convergent relationship in social perception for each of the three races.